2(z-1)=4(z+5)-10

Simple and best practice solution for 2(z-1)=4(z+5)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(z-1)=4(z+5)-10 equation:


Simplifying
2(z + -1) = 4(z + 5) + -10

Reorder the terms:
2(-1 + z) = 4(z + 5) + -10
(-1 * 2 + z * 2) = 4(z + 5) + -10
(-2 + 2z) = 4(z + 5) + -10

Reorder the terms:
-2 + 2z = 4(5 + z) + -10
-2 + 2z = (5 * 4 + z * 4) + -10
-2 + 2z = (20 + 4z) + -10

Reorder the terms:
-2 + 2z = 20 + -10 + 4z

Combine like terms: 20 + -10 = 10
-2 + 2z = 10 + 4z

Solving
-2 + 2z = 10 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
-2 + 2z + -4z = 10 + 4z + -4z

Combine like terms: 2z + -4z = -2z
-2 + -2z = 10 + 4z + -4z

Combine like terms: 4z + -4z = 0
-2 + -2z = 10 + 0
-2 + -2z = 10

Add '2' to each side of the equation.
-2 + 2 + -2z = 10 + 2

Combine like terms: -2 + 2 = 0
0 + -2z = 10 + 2
-2z = 10 + 2

Combine like terms: 10 + 2 = 12
-2z = 12

Divide each side by '-2'.
z = -6

Simplifying
z = -6

See similar equations:

| 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 | | x^(2/3)-2x^(1/3)-8=0 | | 11-6y-19=7y+8-5y | | 6x+2+3x=9x+2 | | 64/5n-8/9=7/15n | | 11y-5y+6=-24-9y | | 6(7x-3)-4=42x-22 | | n^2-4n-35=0 | | 4y+9=-2y-9 | | 11=8x-8 | | W=1925+-550t | | 2/3d+2/3=8/9 | | (a^8b^4)(-a^2b)= | | 6+2y=7y-2.4 | | -2x+8=-100+7x | | F/5-2.2=-2.5 | | 11+-3x=12-20 | | 2x+3(x-9)=2(x+3) | | 4(8x+9)14y=56 | | 1/6+2y=7y-5/12 | | 2-5x=-14x | | 5n-7=5n-10 | | (2x^3z)(81x^4z^2)(5z)(x^6z^3)= | | -34=3d+8/3 | | (2y-7)(2y-7)=12 | | m-14/a=-27 | | 4x+5=3-2x | | 6m=-1/3 | | (8x-12)+x+(2x+5)=180 |

Equations solver categories